A Different Type of Micro-Perforate Hymen: Micro Three-Hole Hymen - Aşırdizer, Mahmut; Sever, Gizem Demet; Oymak, İsmail and Tilki, İsmail (The Bulletin of Legal Medicine, 2021)
Developmental abnormalities of hymen occur as a result of failures in breaking or rupturing the genital tubercle within embryological phase. Cribriform hymen, septal hymen, anterior displaced hymen, imperforate hymen and rigid or elastic hymen are variations of the embryologic development of the hymen. Also microperforate hymen is defined as different type of imperforate hymen which has a small opening. In this article, we reported a different type of microperforate hymen limited reported in the literature. A 17-year-old female case was applied forensic medicine polyclinic for sexual abuse examination at the request of the prosecutor. Any traumatic lesion was not seen in the extra-genital and genital examination. At first glance, hymen looked like an imperforate hymen. When it was carefully investigated, and consulted to gynecology and obstetrics specialist, three crescent-shaped holes seen on it. This was evaluated as a previously unspecified type in the literature of microperforate hymen.